The Nexus between International Humanitarian Law and Peacebuilding in Africa: A Comprehensive Assessment of Preventive Mechanisms - Abraham Ename Minko (Journal of Political Science: Bulletin of Yerevan University)
This article is a comprehensive study that examines the complex and symbiotic relationship between international humanitarian law and peacebuilding in the African context. The article examines the crisis and humanitarian dimensions, focusing on the potential of African countries in conflict prevention and resolution. In this context, it takes into account the peace and conflict characteristics of Africa, which are characterized by a complex interplay of factors including political instability, ethnic tensions, competition for resources and external interventions. This study highlights the key role of the nexus between international humanitarian law and peacebuilding in Africa’s quest for peace, stability and development. By embracing this synergistic relationship, African governments, regional organizations and the international community can contribute to a comprehensive and holistic approach to conflict prevention and resolution. Addressing the challenges and limitations identified is imperative to unlocking the transformative potential of this nexus and paving the way for a more peaceful and prosperous African continent. The article highlights the urgency of preventing and mitigating these conflicts, thereby seeking to clarify how international humanitarian law and peacebuilding can function as complementary pillars in the pursuit of sustainable peace and security. By examining the practical application of these mechanisms, the study elucidates how they contribute to the prevention of armed conflict and the promotion of durable peace. Implementation gaps, where the principles of international humanitarian law are not effectively translated into practice, remain a persistent problem. Furthermore, the prevalence of political interests among the parties involved can hinder peacebuilding efforts, leading to the perpetuation of conflicts. Resource limitations in African countries, both in terms of funding and capacity, pose significant obstacles to the full realization of the potential of international humanitarian law and resilient peacebuilding.